Pattern self-medication use of analgesics in Pune, Maharashtra, India - Jaiswal, Shruti; Keche, Yogendra N.; Yegnanarayan, Radha; Gajendra, Giriraj; Chandanwale, Kshitija; Lanke, Vinaya; Jain, Surabhi; Dakua, Aditi; Das, Gourav; Bhat, Aishwarya; Belvi, Sailee; Desai, Anandita (International Journal of Research in Medical Sciences, 2017)
Background: Objective of current study was to find out self-medication pattern and to study awareness of ADRs to analgesics self-medication. Methods: II MBBS students collected the information of names of analgesics self-medication, dose, frequency of administration, health related problem for use of self-medication, source of information for the use of self-medication and information about ADRs. Students also educated the population about ADRs to analgesics with the help of ADR checklist. Results: Paracetamol was most commonly taken as self-medication and 39% persons reported ADRs with paracetamol. Ibuprofen, diclofenac, paracetamol and aspirin were taken less than WHO DDD for joint pain. 79% study population was ignorant about ADRs to analgesics. Headache (37%) was common health related problem for self-medication of analgesics. Conclusion: Information about problems with repeated use of analgesics like liver damage, analgesic nephropathy, gastric ulceration/bleeding should be provided by pharmacists either orally or with the help of leaflets or display board. Headache is common health related problem for the use of analgesics as self-medication. Pharmacists should take help of assistance tool to diagnosis headache like screener for migraine and guidelines for chronic headache for timely visit of self-medicating person to physician.